Theoretical Fundamentals of Practical Work From Natural Materials in Primary School Technology Courses - Suyundikova Maqsuda Shotemirovna (International Journal on Orange Technologies, 2021)
As we all know, the science of technology was introduced instead of the science of labor education and was enriched with a lot of news and literature. This article discusses the use of natural materials in technology classes in the primary grades, new methods of their use, as well as their theoretical basis